2019
DOI: 10.1016/j.diabres.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of heterogeneity in statin-associated type 2 diabetes mellitus risk: A meta-analysis of randomized controlled trials and observational studies

Abstract: AIMS:To conduct a meta-analysis of statin-associated type 2 diabetes mellitus (T2D) risk among randomized controlled trials (RCTs) and observational studies (OBSs), excluding studies conducted among secondary prevention populations. METHODS:Studies were identified by searching PubMed (1994-present) and EMBASE (1994present). Articles had to meet the following criteria: 1) follow-up >one year; 2) >50% of participants free of clinically diagnosed ASCVD; 3) adult participants ≥30 years old; 4) reported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…primary and secondary CVD prevention) reported a 9 to 55% increased risk of T2DM in statin users compared with statin non-users [ 75 77 ]. In a recent meta-analysis/meta-regression with more than 4 million participants (statins vs no statins) aged ≥ 30 years, older participants were associated with a decreased risk of T2DM (RR 0.79 [95% CI 0.63–0.98] per 10-year older) compared with younger participants [ 76 ]. The reported increase in statin-associated T2DM risk is mainly evident in participants who already are at a high risk to acquire DM (e.g., people with other elements of the metabolic syndrome) [ 75 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…primary and secondary CVD prevention) reported a 9 to 55% increased risk of T2DM in statin users compared with statin non-users [ 75 77 ]. In a recent meta-analysis/meta-regression with more than 4 million participants (statins vs no statins) aged ≥ 30 years, older participants were associated with a decreased risk of T2DM (RR 0.79 [95% CI 0.63–0.98] per 10-year older) compared with younger participants [ 76 ]. The reported increase in statin-associated T2DM risk is mainly evident in participants who already are at a high risk to acquire DM (e.g., people with other elements of the metabolic syndrome) [ 75 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the statin-ASCVD RRs, for which we only used published estimates from randomized controlled trials (RCTs), we considered meta-analytic estimates from RCTs and observational studies when quantifying statin-associated T2D risk: RR = 1.11 (RCTs only), RR = 1.32 (RCT and observational study pooled), and RR = 1.55 (observational studies only). This decision was motivated by previous reports documenting the potential for industry-funded RCTs to underreport adverse drug reactions [15,32], the observation that confounding by factors that affect treatment assignment (i.e., "confounding by indication") is less likely in studies of adverse drug reactions [33], and the average shorter duration (2.6 years) of RCTs compared to observational studies [15].…”
Section: Plos Medicinementioning
confidence: 99%
“…Heterogeneity by sex in age-specific ASCVD incidence rates also is long-described [43], which could further decrease the net benefits of statin therapy for ASCVD reduction. Interestingly, available studies also support the potential for net harms to be greater in females than males [15,16,44,45]. For example, the Justification for the Use of statins in Prevention: an Intervention Trial Evaluating Rosuvastatin (JUPITER) trial reported a 50% increase in physicianreported T2D in females compared to males, corresponding to an estimated 11 incident T2D diagnoses per 1,000 females taking statins over 1.9 years [16].…”
Section: Plos Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…However, Possible Diabetes association with statins therapy has begun discussion in the medical community [5]. Meta-analyses of randomized clinical trials of lipid-lowering with statins suggest that individuals assigned statins were at slightly increased, approximately 9%-12%, in risk of type 2 diabetes mellitus (T2DM) compared with those assigned placebo or standard care [6,7,8]. Since the incidence of this effect cannot be ignored, especially for certain populations, this review aims to examine the relationship between statin treatment and the presence of diabetes.…”
Section: Introductionmentioning
confidence: 99%